ChemInform Abstract: Zinc(II)‐Catalyzed Oxidation of Alcohols to Carbonyl Compounds with Chloramine‐T. Issue 22 (13th May 2013) - Wang, Peng; Cai, Jin; Yang, Jiabin; Sun, Chunlong; Li, Lushen; Hu, Huayou; Ji, Min
Abstract Various primary and secondary alcohols are rapidly oxidized without overoxidation to carboxylic acids.